The Effect of Referral on Achieving Textual cohesion in the Verses of Supplication in the Holy Qur’an - انتظار قاسم ساجت , الباحثة; فليح خضير شني, أ. د. (lark, 2021)
This research shows the textual cohesion in the verses of supplication in the Holy Qur’an through the means of referral, which is the most prominent means of grammatical consistency in analyzing the text and standing on its coherence.  Referral, and then mention the most prominent results.
Keywords: Reference, Grammatical cohesion, supplication verses